Persistent order due to transiently enhanced nesting in an electronically excited charge density wave - L. Rettig (Nature Portfolio, 2016)
Whilst excited electronic states may exhibit unique non-equilibrium behavior, order is inhibited by fluctuations. Here, the authors use femtosecond photoemission spectroscopy to demonstrate transient stabilization of charge density wave order in rare earth tritellurides after near-infrared excitation.